2015
DOI: 10.1038/emm.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-D-glucosamine kinase interacts with dynein light-chain roadblock type 1 at Golgi outposts in neuronal dendritic branch points

Abstract: N-acetylglucosamine kinase (GlcNAc kinase or NAGK) is a ubiquitously expressed enzyme in mammalian cells. Recent studies have shown that NAGK has an essential structural, non-enzymatic role in the upregulation of dendritogenesis. In this study, we conducted yeast two-hybrid screening to search for NAGK-binding proteins and found a specific interaction between NAGK and dynein light-chain roadblock type 1 (DYNLRB1). Immunocytochemistry (ICC) on hippocampal neurons using antibodies against NAGK and DYNLRB1 or dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 42 publications
(55 reference statements)
6
37
0
Order By: Relevance
“…We previously showed that NAGK interacts with DYNLRB1 and NAGK-dynein-Golgi tripartite interactions occur in somata and dendrites, especially in dendritic branch points in stage 4 neurons, and that the NAGK-DYNLRB1 interaction is critical during dendritogenesis ( Islam et al, 2015 ). To investigate NAGK-dynein-Golgi colocalization in axons, we conducted a proximity ligation assay (PLA) using anti-NAGK and anti-TGN38 antibodies followed by ICC with anti-tubulin antibody in stage 3 hippocampal neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that NAGK interacts with DYNLRB1 and NAGK-dynein-Golgi tripartite interactions occur in somata and dendrites, especially in dendritic branch points in stage 4 neurons, and that the NAGK-DYNLRB1 interaction is critical during dendritogenesis ( Islam et al, 2015 ). To investigate NAGK-dynein-Golgi colocalization in axons, we conducted a proximity ligation assay (PLA) using anti-NAGK and anti-TGN38 antibodies followed by ICC with anti-tubulin antibody in stage 3 hippocampal neurons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An 18-amino acid peptide termed ‘DYNLRB1 (59–76)’ and a 23-amino acid peptide termed ‘DYNLRB1 (74–96)’, which were both derived from the NAGK-binding region of DYNLRB1, were custom made by Anygen (Korea) at a purity of 98%. Peptide transfection was performed in neurons after 24 h of plating with a Chariot protein transfection kit (Active Motif, California) using a modified version of the manufacturer’s instructions as previously described ( Islam et al, 2015 ). After incubation for 48 h, neurons were fixed and stained using a β-galactosidase staining kit (Active Motif).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DYNLRB protein sequence is highly conserved among different species; with two isoforms, DYNLRB1 and DYNLRB2, sharing 98% sequence similarity in mammals [13]. Mammalian DYNLRB1 has been studied mainly as an adaptor linking specific modules to the dynein complex, including SMAD2 complexes activated by TGFβ receptors [11,[14][15][16][17][18] and Rab6 or N-acetyl-Dglucosamine kinase (NAGK) for interactions with the Golgi compartment [19][20][21].…”
Section: Introductionmentioning
confidence: 99%